The preparation of children for day surgery from the parent's viewpoint: A mixed methods study - Heli Kerimaa; Mervi Hakala; Marianne Haapea; Willy Serlo; Tarja Pölkki (Wiley, 2024)
Abstract Aim The purpose of the study was to describe the preparation of children for day surgery from the parent's viewpoint. Design Empirical Research Mixed Method. Methods The research applied a mixed‐methods study design. The study was conducted at the Paediatric Day Surgical Department of one REDACTED between 2018 and 2020 at the same time as an associated randomised controlled conduct trial. Parents of 41 children (ages 2-6 years) completed measures assessing their preparation for day surgery and satisfaction with the procedure. Semi‐structured interviews were conducted with 15 parents to better understand their experiences. Results According to the results, most of the parents (95%) told their children about the upcoming day surgery procedure. The child was prepared for the surgery with cognitive and sensory information, and the preparation usually started at home well before the surgery. The parents' experiences with the most critical aspects of preparing their child included three main categories: (1) usability of the preparation method; (2) content and timing of the preparation method and (3) consideration of the family perspective.